Inequality in India: A review of levels and trends - Himanshu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper contributes to the literature by reviewing levels, trends, and structure of inequality since the early 1990s in India. It draws extensively on the existing literature, supplemented with analyses of multiple data sources, to paint a picture. It notes where different data sources suggest conflicting conclusions that reflect both data challenges and the complexity of the underlying drivers of inequality changes. While the primary focus is on examining trends based on standard economic indicators of income/consumption and wealth, the paper briefly reviews distributions of selected non-monetary indicators, such as education and health.
Keywords: 330; consumption; data challenges; inequality; income; non-monetary indicators; wealth